Discharge Delay in Patients with Community-Acquired Pneumonia Managed on a Critical Pathway - Jeremy J Moeller; Martin Ma; Paul Hernandez; Thomas Marrie; Claire Touchie; Ward Patrick (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: It has previously been reported that a critical pathway for community-acquired pneumonia (CAP) significantly reduces bed days per patient managed but results in no difference in average length of stay, suggesting that discharge criteria were not successfully implemented. The present study sought to identify factors in the timing of discharge not taken into account by discharge criteria.